PEMBUATAN MIKROORGANISME LOKAL (MOL) DARI JEROAN IKAN - Widya Safitri; Sri Novalina A; Azwin Apriandi (Marinade, 2023)
Increasing the economic value of fish innards by processing them into one of the more useful products is Local Microorganisms (MOL). MOL is a decomposer in the manufacture of organic fertilizer in this study can be made from waste with fish offal as the basic ingredient. This study aims to determine the production of local microorganisms (MOL) and the MOL content of fish offal. The method used in the process of making MOL is fermented fish offal. Samples of fish offal MOL that had been successfully fermented for 14 days were then tested for TPC using Media Plate Count Agar. Isolation of Lactic Acid Bacteria (LAB) will be tested using MRS Agar + 1% used to differentiate LAB from non-acid producing bacteria. While the findings of mushroom identification using Potato Dextrose Agar. The results of the research that has been done show that the composition of 500 grams of fish offal, 1 liter of coconut water and 3 ounces of brown sugar in the manufacture of MOL from fish offal shows a bacterial count of 6.85x CFU/ml, which does not exceed the TPC standard threshold. The results of isolation of lactic acid bacteria found that bacteria in MOL from fish offal, namely Lactobacillus, identified the growth of fungi, where the fungi in MOL are beneficial for plant development from amino acids and sugars secreted by photosynthetic bacteria, organic matter and plant roots.